1976
DOI: 10.1073/pnas.73.11.4050
|View full text |Cite
|
Sign up to set email alerts
|

Subcellualr distribution of protein carboxymethylase and its endogenous substrates in the adrenal medulla: possible role in excitation-secretion coupling.

Abstract: Protein carboxymethylase (S-adenosyl-L-methionine:protein O-methyltransferase, EC 2.1.1.24) transfers a methyl group from S-adenosyl-L-methionine to carboxyl side chains of proteins to form labile protein-methyl esters which, thus, neutralize negative charges. This enzyme was examined for its possible participation in excitation-secretion coupling in the adrenal medulla. Protein carboxymethylase has a specific activity several times higher in the adrenal medulla than in the adrenal cortex; also, the medulla ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(32 citation statements)
references
References 22 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…There is in fact a history of ideas regarding a role for PIMT (when it was known as PCMT or PCM) in the regulation of neurotransmission and neurotransmitter receptor activity, (reviewed in [84]). Diliberto et al found in 1976 that carboxymethylation by this enzyme led to release of membrane proteins from chromaffin granules of the adrenal medulla and proposed that methylation was important for excitation-secretion coupling [85]. However, this hypothesis was later contested based on studies of protein secretion in the pancreas and parotid gland [86].…”
Section: A Special Role For Pimt In the Brain And Testes?mentioning
confidence: 97%
“…There is in fact a history of ideas regarding a role for PIMT (when it was known as PCMT or PCM) in the regulation of neurotransmission and neurotransmitter receptor activity, (reviewed in [84]). Diliberto et al found in 1976 that carboxymethylation by this enzyme led to release of membrane proteins from chromaffin granules of the adrenal medulla and proposed that methylation was important for excitation-secretion coupling [85]. However, this hypothesis was later contested based on studies of protein secretion in the pancreas and parotid gland [86].…”
Section: A Special Role For Pimt In the Brain And Testes?mentioning
confidence: 97%
“…In the homogenate assay for protein carboxymethylase a standard incubation time of 15 min has been used elsewhere [9][10][11]. This was used here as well since the rate of incor poration decreased with longer incubation periods ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…The background value obtained from incubation at 0°C was subtracted from that at 37°C to obtain the level of specific activity. [ 10] Conceptuses were rinsed in PBS+5 mg/ml glucose, suspended in 0.3 M sucrose at 10 mg protein per millilit er, minced, and homogenized in a Dounce homogenizer (5 strokes A pestle and 5 strokes B pestle). Samples were then removed for Lowry protein determinations.…”
Section: Intact Cell Assay O F Protein Carboxymethylation Activitymentioning
confidence: 99%
“…Diliberto et al [20] considered the possi bility that a similar carboxymethylation of protein would by reduction of negative charges modulate cell secretory function. Subsequent investigation of protein carboxymethylation appears to indicate that the protein carboxy methylation is associated only with abnormal amino acids and is not involved in direct reg ulation of eukaryotic cell function [21].…”
Section: Discussionmentioning
confidence: 99%